Aqueous Redox Flow Battery Suitable for High Temperature Applications Based on a Tailor‐Made Ferrocene Copolymer. Issue 41 (25th September 2020) - Borchers, Philipp S.; Strumpf, Maria; Friebe, Christian; Nischang, Ivo; Hager, Martin D.; Elbert, Johannes; Schubert, Ulrich S.
Abstract: Water‐soluble, and ferrocene‐containing methacrylamide copolymers with different comonomer ratios of the solubility‐promoting comonomer [2‐(methacryloyloxy)‐ethyl]‐trimethylammonium chloride (METAC) are synthesized in order to obtain a novel, temperature‐stable electrolyte for aqueous redox flow batteries. The electrochemical properties of one chosen polymer are studied in detail by cyclic voltammetry and rotating disc electrode (RDE) investigations. Additionally, the diffusion coefficient and the charge transfer rate are obtained from these measurements. The diffusion coefficient from RDE is compared to the value from synthetic boundary experiments at battery concentrations, using an analytical ultracentrifuge, yielding diffusion coefficients of a similar order of magnitude. The polymer is further tested in a redox flow battery setup. While performing charge and discharge experiments against the well‐established bis ‐(trimethylammoniumpropyl)‐viologen, the polymer reveals high columbic efficiencies of >99.8% and desirable apparent capacity retention, both at room temperature as well as at 60 °C. Further experiments are conducted to verify the stability of the active compounds under these conditions in both charge states. Lastly, the electrochemical behavior is linked to the characteristics of the polymers concerning absolute values of the molar mass and diffusion coefficients. Abstract : A new ferrocene containing monomer is synthesized and its copolymerization with a water‐solubility promoting comonomer is investigated. The electrochemical and solution characteristics of a corresponding polymer are studied in detail. With a coulombic efficiency of >99.8% in an aqueous redox flow battery setup at 60 °C, a cheap, robust system for use at elevated temperatures is presented.